1950
DOI: 10.1128/mmbr.14.2.115-160.1950
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcus Carrier Rates and Meningitis Incidence 1

Abstract: The purpose of this paper is to review certain general features of the epidemiology of meningococcus meningitis in the light of a survey of meningococcus carriage which was carried on continuously from December, 1941, to May, 1945, with a final carrier test in December, 1946. This was part of a survey including hemolytic streptococci, Corynibacterium diphtheriae and Hemophilus influenzae, which was conducted by the Commission on Pre-epidemic Survey in the First Service Command under the Board for the Investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In military recruits and among laboratory personnd, carrier-induced antimeningococcal antibodies have been shown to persist at high titer for a minimum of 4 to 6 months after exposure. This provides a reasonable explanation for the universal observation (17)(18)(19) that seasoned military personnd are much less susceptible to meningococcal disease than are basic recruits. Such seasoned troops have apparently been immunized during basic training by means of the meningococcal carrier state.…”
Section: Discussionmentioning
confidence: 71%
“…In military recruits and among laboratory personnd, carrier-induced antimeningococcal antibodies have been shown to persist at high titer for a minimum of 4 to 6 months after exposure. This provides a reasonable explanation for the universal observation (17)(18)(19) that seasoned military personnd are much less susceptible to meningococcal disease than are basic recruits. Such seasoned troops have apparently been immunized during basic training by means of the meningococcal carrier state.…”
Section: Discussionmentioning
confidence: 71%
“…In the latter study, meningococcal carrier rates in the crowded sleeping quarters approached those of our study only when the British soldiers slept on cots 2.5 feet wide and less than 9 inches apart. Although the authors of several studies among American military populations concluded that there was no correlation between crowding of sleeping quarters and carrier rates, severe crowding (sufficient to provide contact spread) was not present in these studies [16,30]. In regard to sleeping arrangements, it was of interest that the presence of a case vs. a carrier in a bedroom did not increase the probability of infection among other persons in that room.…”
Section: Discussionmentioning
confidence: 93%
“…However, these two studies were both conducted during epidemics involving group A strains. Aycock and Muller (19) showed that the carriage rate of group A rises in healthy individuals during group A epidemics. It has to be noted that no epidemic of meningococcal disease occurred in this locality throughout the duration of this carriage study.…”
Section: Discussionmentioning
confidence: 99%